2011
DOI: 10.1051/0004-6361/201117116
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for helicity in explosive events

Abstract: Aims. We report spectroscopic observations in support of a novel view of transition region explosive events, observations that lend empirical evidence that at least in some cases explosive events may be nothing else but spinning narrow spicule-like structures. Methods. Our spectra of textbook explosive events with simultaneous Doppler flow of a red and a blue component are extreme cases of high spectroscopic velocities that lack apparent motion, to be expected if interpreted as a pair of collimated, linearly m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 29 publications
3
50
1
Order By: Relevance
“…Edison Pettit first noticed this type of prominences and categorized them as tornadoes (Pettit 1943). More recently, the term tornado has also been used to describe some other rotating solar phenomena including the macrospicules with rotating motions 1 School of Earth and Space Sciences, Peking University, 100871 Beijing, China; huitian@pku.edu.cn 2 Max-Planck Institute for Solar System Research, Justus-von-Liebig-Weg 3, D-37077 Göttingen, Germany 3 Key Laboratory of Dark Matter and Space Astronomy, Purple Mountain Observatory, Chinese Academy of Sciences, Nanjing, Jiangsu, China (Pike & Mason 1998;Curdt & Tian 2011), chromospheric swirls which may channel energy to the corona (Wedemeyer-Böhm & Rouppe van der Voort 2009;Wedemeyer-Böhm et al 2012;Yang et al 2015) and fast-evolving tornado-like erupting structures (Chen et al 2017). Other rotating structures such as coronal cyclones rooted in the rotating network magnetic field (Zhang & Liu 2011) and rotating jet-like structures (e.g., Shen et al 2011Shen et al , 2012 have also received attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Edison Pettit first noticed this type of prominences and categorized them as tornadoes (Pettit 1943). More recently, the term tornado has also been used to describe some other rotating solar phenomena including the macrospicules with rotating motions 1 School of Earth and Space Sciences, Peking University, 100871 Beijing, China; huitian@pku.edu.cn 2 Max-Planck Institute for Solar System Research, Justus-von-Liebig-Weg 3, D-37077 Göttingen, Germany 3 Key Laboratory of Dark Matter and Space Astronomy, Purple Mountain Observatory, Chinese Academy of Sciences, Nanjing, Jiangsu, China (Pike & Mason 1998;Curdt & Tian 2011), chromospheric swirls which may channel energy to the corona (Wedemeyer-Böhm & Rouppe van der Voort 2009;Wedemeyer-Böhm et al 2012;Yang et al 2015) and fast-evolving tornado-like erupting structures (Chen et al 2017). Other rotating structures such as coronal cyclones rooted in the rotating network magnetic field (Zhang & Liu 2011) and rotating jet-like structures (e.g., Shen et al 2011Shen et al , 2012 have also received attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports in the literature concerning the accumulation and expulsion of relative magnetic helicity in the magnetic network and quiet-Sun regions in general and this mechanism's role in quiet-Sun dynamics; only Zhao et al (2009) have investigated current helicity budgets in A&A 564, A86 (2014) network bright points. However, there exist reports (Jess et al 2009;Curdt & Tian 2011;De Pontieu et al 2012) that argue for torsional oscillations in fine structures, such as explosive events and spicules, thus suggesting the existence of twisting motions that could lead to expulsion or transfer of helicity to larger scales in the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…With generation of both helicity and energy mostly concentrated along the network, our analysis suggests that there is sufficient free energy in the network to power fine-scale structures residing at the network via dissipative processes, such as magnetic reconnection. Although there is currently substantial observational evidence (Jess et al 2009;Curdt & Tian 2011;De Pontieu et al 2012;Tsiropoula et al 2012;De Pontieu et al 2014) for the presence of helical behavior and twist in small structures, such as mottles and spicules, complemented by some simulations on larger polar-jet structures (Pariat et al 2009) Tziotziou et al (2014a). Verification of these values is still pending and as the three-dimensional magnetic field configuration cannot be inferred from observations, it relies on a combination of high-resolution magneto-hydrodynamic helicity simulations in fine-scale structures with high-resolution chromospheric observations.…”
Section: Discussionmentioning
confidence: 99%
“…There are no quantitative estimations of the helicity stored and/or carried by fine-scale structures, such as mottles and spicules, although there exist reports in literature (Jess et al 2009;Curdt & Tian 2011;De Pontieu et al 2012;Tsiropoula et al 2012) that such structures often show a helical behavior. Recent observations with NASA's Interface Region Imaging Spectrograph (IRIS) have shown that even the quiet-Sun chromosphere and transition region, in sub-arcsec scales, are filled with twist or torsional motions (De Pontieu et al 2014).…”
Section: Energy and Helicity Budgets Of Quiet-sun Regionsmentioning
confidence: 99%
See 1 more Smart Citation